Falter [compact disc, unabridged] : has the human game begun to play itself out? - McKibben, Bill (Macmillan Audio, 2019)
Shares cautionary insights into how emerging technologies, including artificial intelligence and robotics, are being developed through fervent ideologies that are threatening the diversity of human experience.